2021
DOI: 10.1088/1361-6528/abd975
|View full text |Cite
|
Sign up to set email alerts
|

Template-free method for the synthesis of high-pore-volume γ-Al2O3 nanofibers in a membrane dispersion microreactor

Abstract: Mesoporous γ-Al2O3 nanofibers with high pore volume and uniform pore size distributions were successfully synthesized via a template-free method in a membrane dispersion microreactor followed by calcination. The effects of crystal temperature, pH values, continuous phase concentration and washing solvent on the γ-Al2O3 nanofibers were carefully studied. The results showed that the as-obtained γ-Al2O3 nanofibers showed a length of 40–60 nm and a width of 3.2–3.4 nm, which were attributed to the high microscopic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 55 publications
(59 reference statements)
0
4
0
Order By: Relevance
“…Benefiting from the high microscopic mixing rate of the membrane dispersion microreactor, the mesoporous γ-Al 2 O 3 nanofibers were synthesized by a simple, template-free and singlephase microfluidic method using NaAlO 2 and Al(NO 3 ) 3 •9H 2 O as raw materials. And the obtained γ-Al 2 O 3 nanofibers showed considerable pore volumes and uniform pore size distributions compared with those prepared by traditional batch stirring methods [129]. The morphology-controlled synthesis of ZnO nanostructures (spindles, sheets and spheres) was reported via the precipitation of Zn(NO 3 ) 2 and NaOH by a facile surfactant-free method in microreactors (under single-phase flow) [130].…”
Section: Metal Oxide Catalystmentioning
confidence: 92%
“…Benefiting from the high microscopic mixing rate of the membrane dispersion microreactor, the mesoporous γ-Al 2 O 3 nanofibers were synthesized by a simple, template-free and singlephase microfluidic method using NaAlO 2 and Al(NO 3 ) 3 •9H 2 O as raw materials. And the obtained γ-Al 2 O 3 nanofibers showed considerable pore volumes and uniform pore size distributions compared with those prepared by traditional batch stirring methods [129]. The morphology-controlled synthesis of ZnO nanostructures (spindles, sheets and spheres) was reported via the precipitation of Zn(NO 3 ) 2 and NaOH by a facile surfactant-free method in microreactors (under single-phase flow) [130].…”
Section: Metal Oxide Catalystmentioning
confidence: 92%
“…Coprecipitation is usually implemented in a stirred tank, but the pore properties of the γ-Al 2 O 3 product obtained via this method are not satisfactory. To overcome the long mass-transfer distance and unsatisfactory mixing performance of stirred tanks, the use of a membrane dispersion microreactor has been investigated. , Wan et al synthesized γ-Al 2 O 3 with a pore volume of 1.52 cm 3 /g and a specific surface area 403.8 m 2 /g under the NaAlO 2 concentration of 1.25 mol/L and the Al 2 (SO 4 ) 3 concentration of 0.25 mol/L. The core structure of a microreactor comprises a stainless steel microfiltration membrane which allows the fluid to be dispersed into tiny droplets with an extremely large interfacial area and short mass-transfer distance in the continuous microchannel, resulting in a substantially improved mass-transfer rate.…”
Section: Introductionmentioning
confidence: 99%
“…A controlled synthesis of nanoscaled metal oxides by tuning the crystallography architecture is aimed for target properties and functions. It has been reported that steel-stainless membrane microreactors were successfully applied to produce dispersed nanosilica, size-controllable CeO 2 nanoparticles, and high-pore-volume γ-Al 2 O 3 nanofibers . The shaped Cu 2 O microcrystals were selectively prepared with the membrane dispersion one-step method based on our previous work …”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that steel-stainless membrane microreactors were successfully applied to produce dispersed nanosilica, 8 size-controllable CeO 2 nanoparticles, 9 and high-pore-volume γ-Al 2 O 3 nanofibers. 10 The shaped Cu 2 O microcrystals were selectively prepared with the membrane dispersion one-step method based on our previous work. 11 Cu 2 O-based photocatalysis and Fenton oxidation could be combined for efficient degradation of organic pollutants driven by both photoenergy and chemical potential.…”
mentioning
confidence: 99%